Komunikowanie ugrupowań politycznych na Facebooku w trakcie kryzysu sejmowego na przełomie 2016 i 2017 roku - Szwed-Walczak, Anna (Polityka i Społeczeństwo, 2020)
The purpose of research was to indicate the political communications of political parties on social media, during political crisis in Poland. It was hypothesized, that the political crisis allowed the promotion of political party platforms among citizens. The research results showed that parties used fanpages on Facebook to politically discredit their political opponents, shaping or promoting their own images. I specified: the subject area of published posts, the kind of posts, form of promotion the image and form of engagement of users. I applied quantitative and qualitative research. Content analysis and comparative methodology were used.